Characterization of phenolic compounds in olive stones of three moroccan varieties - Mustapha Elbir (Maderas: Ciencia y Tecnología, 2015)
Phenolic compounds have a fundamental importance in the nutritional and sensorial characteristics of olive. In this study phenolic compounds extracted from olive fruit stones of three Moroccan registered cultivars were analyzed. The obtained results showed that the total amount of phenolic compounds varied according to the olive variety. The stones of the Moroccan Picholine variety were the richest in total phenolic compounds (11,32 mg of gallic acid equivalent (GAE)/g of dry weight (DW)) followed by Haouzia (4,55 mg GAE/g DW) and Menara (3,56 mg GAE/g DW). The qualitative analysis showed that the analyzed extracts were predominated by nuzhenide and its derivatives. Thus nuzhenide was observed among the major compound in the three studied cultivars. Its mono, di and tri 11-methyl oleoside adducts were also detected. Various compounds with the same molecular weight values and corresponding to nuzhenide or its derivatives were detected indicating the presence of various isomers.